Análise da experiência educativa dos jovens eadultos do Colegio Estadual Benta Pereira en campos dos goytacazes/RJ, Brasil a luz da pedagogía Salesiana - Fernandes Coelho, María de Fátima (2011)
This study is due to analyze the educational experience among youngs and adults from Benta Pereira State School in the city of Campos dos Goytacazes / RJ, Brazil in light of the Salesian Pedagogy. First it has been resumed the history of Youngs and Adults Education Program (EJA) from 1930 emphasizing the political orientation guidelines from this way of teaching. Then we presented the EJA students profile. Addressing the right to education and preparation for work, as well as the principles of the Salesian Pedagogy we aimed, by comparing with the legal frameworks of adult education (EJA), verify if the humanistic approach was also present in the first considered by the legislation. It is a qualitative research being conducted a case study. Bibliographical research, questionnaires and interviews were the instruments used in this study. The research roots are the following categories: A pesquisa alicerçou-se nas categorias: right to education, job training and Salesian Pedagogy principles. From this investigation, the results pointed to develop actions to improve the educational activities and educational management in the light of that pedagogy, which includes the pedagogical and methodological development with a humanist bias with humanistic and effective opportunities to promote training work in the binomial and citizenship.